A comparative study on performance of manufacturing systems from an agility perspective using simulation. (1st January 2014) - Sabu, K.; Krishnankutty, K.V.
Agility is the ability to respond rapidly and effectively to current and future configuration of market demand with respect to time. Production layout planning takes an increasingly important role to enhance the agile manufacturing of products. This paper seeks to make a contribution by providing insight from the evaluation of three manufacturing systems to find out the best one that enhances agility in manufacturing. Simulation using ARENA TM software has been performed to study and compare the important agility performance measures of process layout, cellular robust design and cellular adaptive design. Both the cellular designs give a lower work in process inventory (WIP) and manufacturing lead time (MLT) compared to process layout, indicating the superiority of agility for cellular systems. Though the improvement in performance of robust design over process layout is marginal, the adaptive design is found to offer a significant improvement of parameters in terms of agility. The proposed cellular layout has promising advantages in a competitive market facing uncertain fluctuations in product demand and product mix.